THE CONCEPT AND TYPES OF LEAVE - Turdikulov Makhtumkuli Mirzakulovich (Ecomind Press, 2025)
The article discusses the social rights of an employee established by national legislation, one of which is rest time. The article discusses the rights of an employee to rest and their requirements.
Keywords: Employee, employer, rest time, break, additional break, holidays.